Rapamycin combined with anti-CD45RB mAb and IL-10 or with G-CSF induces tolerance in a stringent mouse model of islet transplantation. - Nicola Gagliani; Silvia Gregori; Tatiana Jofra; Andrea Valle; Angela Stabilini; David M Rothstein; Mark Atkinson; Maria Grazia Roncarolo; Manuela Battaglia (PLoS ONE)
Background A large pool of preexisting alloreactive effector T cells can cause allogeneic graft rejection following transplantation. However, it is possible to induce transplant tolerance by altering the balance between effector and regulatory T (Treg) cells. Among the various Treg-cell types, Foxp3(+)Treg and IL-10-producing T regulatory type 1 (Tr1) cells have frequently been associated with tolerance following transplantation in both mice and humans. Previously, we demonstrated that rapamycin+IL-10 promotes Tr1-cell-associated tolerance in Balb/c mice transplanted with C57BL/6 pancreatic islets. However, this same treatment was unsuccessful in C57BL/6 mice transplanted with Balb/c islets (classified as a stringent transplant model). We accordingly designed a protocol that would be effective in the latter transplant model by simultaneously depleting effector T cells and fostering production of Treg cells. We additionally developed and tested a clinically translatable protocol that used no depleting agent. Methodology/principal findings Diabetic C57BL/6 mice were transplanted with Balb/c pancreatic islets. Recipient mice transiently treated with anti-CD45RB mAb+rapamycin+IL-10 developed antigen-specific tolerance. During treatment, Foxp3(+)Treg cells were momentarily enriched in the blood, followed by accumulation in the graft and draining lymph node, whereas CD4(+)IL-10(+)IL-4(-) T (i.e., Tr1) cells localized in the spleen. In long-term tolerant mice, only CD4(+)IL-10(+)IL-4(-) T cells remained enriched in the spleen and IL-10 was key in the maintenance of tolerance. Alternatively, recipient mice were treated with two compounds routinely used in the clinic (namely, rapamycin and G-CSF); this drug combination promoted tolerance associated with CD4(+)IL-10(+)IL-4(-) T cells. Conclusions/significance The anti-CD45RB mAb+rapamycin+IL-10 combined protocol promotes a state of tolerance that is IL-10 dependent. Moreover, the combination of rapamycin+G-CSF induces tolerance and such treatment could be readily translatable into the clinic.